Design and Implementation of Quality Inspection System for Image on National Platform for Geospatial Information Services in China - C. Wang; Z. Wang; H. Zhang; D. Tang; L. Ding (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This article is based on the data update characteristics of the online service for National Platform for Geospatial Information Services (TIANDITU) imagery data, and it designs and implements a full-process imagery data quality inspection system specifically for imagery tile data. The development and application of this system have made the quality inspection and update process of TIANDITU imagery data more scientific and efficient, significantly enhancing the efficiency of the quality inspection and update process for TIANDITU imagery data. The article provides a detailed introduction to the system’s architecture, design, implementation, characteristics and application. It also proposes optimizations to be made in algorithm optimization, user interface, and system stability. This article provides new ideas for quality inspection and publishing based on image tile data.